Immuno Systems Biology A macroscopic approach for immune cell signaling - Selvarajoo, Kumar. (Systems Biology,, 2013)
Technological advances of modern biology have generated high volumes of omics data. The natural precedence has been to put the complex information together, so that it will lead to spectacular scientific discoveries and medical breakthroughs. In this light, tremendous efforts worldwide are reshaping biological research by integrating with information science. Despite the systems biology efforts, for major illnesses, such as proinflammatory diseases and cancer, there is clear clinical evidence that even the most current therapies, at best, control transient response and subdue to the robust adaptability of the disease state. Hence, there is a need for system-levels understanding of bio-complexity. Kumar Selvarajoo brings attention to fundamental questions governing sophisticated behaviors of the mammalian immune system. To tackle some of the complex issues, the book introduces perturbation-response approach, using the law of physics (mass flow conservation), as a means to interpret the dynamic response of major proinflammatory pathways of the immune and cancer cells. Overall, the book provides an illustrated journey that explains biological cell signaling in simple terms.